2021
DOI: 10.1002/cti2.1249
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antigen‐specific T‐cells targeting seven viral and fungal pathogens after allogeneic haemopoietic stem cell transplant

Abstract: Objectives. Adoptive immunotherapy using donor-derived antigen-specific T-cells can prevent and treat infection after allogeneic haemopoietic stem cell transplant (HSCT). Methods. We treated 11 patients with a prophylactic infusion of 2 9 10 7 cells per square metre donor-derived T-cells targeting seven infections (six viral and one fungal) following HSCT. Targeted pathogens were cytomegalovirus (CMV), Epstein-Barr virus (EBV), adenovirus, varicella zoster virus, influenza, BK virus (BKV) and Aspergillus fumig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Although FSTs have been shown to increase the resistance against Aspergillus fumigatus infection or prolong the survival of mice with invasive pulmonary mycosis [59][60][61], as of today, and in contrast to the numerous VST trials, there are only two completed, clinical trials of adoptive T cell immunotherapy against fungal diseases [41,62]. In the first study, conducted 16 years ago, Perrucio et al showed that the administration of anti-Aspergillus T cell clones was safe, enhanced the control of Aspergillus antigenemia and improved the survival of transplanted patients with invasive aspergillosis as compared to the control cohort not receiving immunotherapy (survived patients 9/10 vs. 7/13, respectively).…”
Section: Harnessing T Cells To Control Fungal Infectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although FSTs have been shown to increase the resistance against Aspergillus fumigatus infection or prolong the survival of mice with invasive pulmonary mycosis [59][60][61], as of today, and in contrast to the numerous VST trials, there are only two completed, clinical trials of adoptive T cell immunotherapy against fungal diseases [41,62]. In the first study, conducted 16 years ago, Perrucio et al showed that the administration of anti-Aspergillus T cell clones was safe, enhanced the control of Aspergillus antigenemia and improved the survival of transplanted patients with invasive aspergillosis as compared to the control cohort not receiving immunotherapy (survived patients 9/10 vs. 7/13, respectively).…”
Section: Harnessing T Cells To Control Fungal Infectionsmentioning
confidence: 99%
“…In the first study, conducted 16 years ago, Perrucio et al showed that the administration of anti-Aspergillus T cell clones was safe, enhanced the control of Aspergillus antigenemia and improved the survival of transplanted patients with invasive aspergillosis as compared to the control cohort not receiving immunotherapy (survived patients 9/10 vs. 7/13, respectively). Since then, only recently, Gottlieb's group evaluated the safety and biological efficacy of administering mobilized donor peripheral blood-derived specific T cells with activity against Aspergillus, CMV, adenovirus, EBV, varicella-zoster virus (VZV), influenza, and BKV, as prophylaxis of fungal and viral reactivation and/or disease following allogeneic HCT [62]. Grade III/IV graft-versus-host disease (GvHD) was developed in 4/11 patients, however, the early prophylactic administration (median 37 days post-HCT) of multipathogen-specific T cells (mp-STs) did not allow the dissociation of the GvHD risk that could be derived from the mp-STs from the GvHD risk originating from the transplant procedure per se, which is expected to be high anyway, early post-transplant.…”
Section: Harnessing T Cells To Control Fungal Infectionsmentioning
confidence: 99%
See 3 more Smart Citations